011 Exploring animal models of delirium during dementia. Issue 10 (24th September 2010) - Cunningham, C
Abstract : Abstract: Delirium is an acute, severe neuropsychiatric syndrome, characterised by cognitive deficits. It is highly prevalent in ageing and dementia and is frequently precipitated by peripheral infections. Delirium is poorly understood and the lack of biologically relevant animal models has limited basic research. We proposed that prior pathology and superimposed systemic inflammation would combine to produce acute impairments relevant to delirium during dementia. Using chronic neurodegeneration induced during prion disease or selective lesioning of the basal forebrain cholinergic nuclei we have developed animal models to address this hypothesis. Normal mice or animals with these prior pathologies were challenged systemically with bacterial endotoxin (lipopolysaccharide (LPS) 100 μg/kg) and assessed on working memory tasks dependent on the brain region showing prior pathology. LPS had no effect on working memory in normal animals but induced significant acute and reversible working memory deficits in animals with either early synaptic loss, or limited basal forebrain lesions. Animals with prior pathology did not show deficits on these tasks in the absence of LPS. The deficits were associated with heightened CNS inflammatory responses to systemic inflammatory stimuli, despite equivalent systemic responses. Prior pathology, including microglial priming, synaptic loss and neuronal death predispose individuals to heightened cognitive deficits upon systemic inflammatory insults. The relevance of these findings for delirium during dementia will be discussed.